“Valuation Bases and Techniques for Natural Resources in Indonesia’s CGFS: A Literature Review and Practical Illustration in Indonesia” - Nugroho, Prayudi; Ambarwati, Ria Dewi; Aisyah Kustiani, Nur (Assets: Jurnal Ekonomi, Manajemen, dan Akuntansi, 2025)
This study addresses the gap in the Central Government Financial Statements (CGFS), in which natural resource stocks have not been recognised even though their economic benefits are reflected in state revenue. This study uses a structured literature review of publications from 2010 to 2024 in various databases with inclusion criteria related to public sector accounting, natural resource valuation, IPSAS, SEEA, and national regulations. The selection process includes identification, elimination of duplication, abstract selection, and full review. The analysis was conducted through narrative-thematic synthesis to identify the application of the main value bases, namely fair value, net present value, and current replacement cost in natural resource valuation. The results show that the integration of natural resource into the CGFS requires harmonisation of standards, clarity of methodology, and data readiness in order to be reliable, fiscally relevant, and auditable.